Catalytic carbonyl hydrosilylations via a titanocene borohydride–PMHS reagent system. Issue 16 (11th July 2017) - Fianu, Godfred D.; Schipper, Kyle C.; Flowers II, Robert A.
Abstract : Catalytic amounts of titanocene(iii ) borohydride, generated under mild conditions from commercially available titanocene dichloride, in concert with a stoichiometric hydride source is shown to effectively reduce aldehydes and ketones to their respective alcohols in aprotic media. Abstract : Reduction of a wide range of aldehydes and ketones with catalytic amounts of titanocene borohydride in concert with a stoichiometric poly(methylhydrosiloxane) (PMHS) reductant is reported. Preliminary mechanistic studies demonstrate that the reaction is mediated by a reactive titanocene(iii ) complex, whose oxidation state remains constant throughout the reaction.